Pengembangan Kartu Domano (Domino Matematika Trigono) Sebagai Media Pembelajaran Pada Matakuliah Trigonometri - Kristian Tantra Sidarta; Tri Nova Hasti Yunianta (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
This research aims is to develop a learning media called Domano Card, that is an abbreviation from Trigono mathematics Dominoes. This media is expected to be valid, effective, and practical to be used as a learning tool for Trigonometry Courses in the college. It is consists of three sets of Domano cards, game boards, and game rules. This Domano Card contains of the pairs of questions and answers. This research type is Research Development (R&D) with ADDIE model (Analyze, Design, Development, Implementation, Evaluate). The subject of this research is 64 active students of Mathematics Education, Satya Wacana Christian University in Trigonometry course. Domano cards are developed based on the students’ learning styles. Validity test was done by 2 validators, there are media experts and material experts It has obtained media feasibility result of 98.71% with very decent category and the result of material feasibility of 92.5% with very decent category. The effectiveness test was done by Paired Samples t-test with SPSS 17. It is indicated that there is a significant differences after the use of Domano Card with the mean value improvement from 57 to 73. The respondents of practicality test are lecturer of Trigonometry course and the lecturer assistant class that obtained 89% with very good category. Based on this development research, it can be concluded that Domano Card media is valid, effective, and practical use as a means of self-learning exercises for students in Trigonometry courses.